2022
DOI: 10.1038/s41564-022-01238-1
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal within-host diversity during colonization, transmission and treatment

Abstract: Characterizing the genetic diversity of pathogens within the host promises to greatly improve surveillance and reconstruction of transmission chains. For bacteria, it also informs our understanding of inter-strain competition and how this shapes the distribution of resistant and sensitive bacteria. Here we study the genetic diversity of Streptococcus pneumoniae within 468 infants and 145 of their mothers by deep sequencing whole pneumococcal populations from 3,761 longitudinal nasopharyngeal samples. We demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 102 publications
0
31
1
Order By: Relevance
“…As a part of larger application pipelines, Themisto has already been instrumental in published metagenomics studies (Tonkin-Hill et al ., 2022; Mäklin et al ., 2022) and is incorporated as part of several other ongoing projects, in particular in the study of antimicrobial resistance. As the size and availability of reference genome data sets continues to grow, we expect our improvements to further drive adoption of Themisto as a standard for constructing and querying these large corpora, and the adaptability of our hybrid method to facilitate discovery of entirely new applications for pseudoalignment.…”
Section: Discussionmentioning
confidence: 99%
“…As a part of larger application pipelines, Themisto has already been instrumental in published metagenomics studies (Tonkin-Hill et al ., 2022; Mäklin et al ., 2022) and is incorporated as part of several other ongoing projects, in particular in the study of antimicrobial resistance. As the size and availability of reference genome data sets continues to grow, we expect our improvements to further drive adoption of Themisto as a standard for constructing and querying these large corpora, and the adaptability of our hybrid method to facilitate discovery of entirely new applications for pseudoalignment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been recently shown that there is an elevated risk of both the acquisition and persistent carriage of multi-drug resistant pneumococci following antimicrobial treatment 43 . The mechanism of persistence of multi-drug resistant pneumococci was attributed to reduced within-host competition following antimicrobial treatment, indicating that in the absence of treatment, susceptible lineages outcompete resistant lineages 43 . In Malawi, as part of standard HIV clinical management, PLHIV are put on daily co-trimoxazole prophylaxis 17, 18 .…”
Section: Discussionmentioning
confidence: 99%
“…This is indicative of a strong selective benefit of the csRNA3 alteration to the virus. Although the modification cannot prevent competence being induced by CSP produced by cells with an unmodified csRNA3 within the same nasopharynx, it should nevertheless be effective, as most individuals carrying pneumococci are singly colonised by cells descended from one recent acquisition [ 96 ]. In cases of multiple colonisation, it is likely that different strains are physically segregated within the nasopharynx as a consequence of interstrain competition mediated by mechanisms such as bacteriocins [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prophage insertions disrupting the pilus gene comYC , which is necessary for competence [ 34 , 89 ], cause loss of function, contrasting with the increased effectiveness of the phage-modified competence-inhibiting ccnCL . The truncation of comYC was recently demonstrated to be the most common single type of protein-modifying mutation affecting coding sequences during within-host pneumococcal evolution [ 96 ]. This emphasises the importance of conflict between prophage and the host cell in rapidly generating common polymorphisms in this bacterium [ 99 ].…”
Section: Discussionmentioning
confidence: 99%